Effects of Granule-Associated Protein PhaP on Glycerol-Dependent Growth and Polymer Production in Poly(3-Hydroxybutyrate)-Producing Escherichia coli - de Almeida, Alejandra (American Society for Microbiology (ASM), 2007)
Polyhydroxyalkanoates (PHAs) are accumulated as intracellular granules by many bacteria under unfavorable conditions, enhancing their fitness and stress resistance. Poly(3-hydroxybutyrate) (PHB) is the most widespread and best-known PHA. Apart from the genes that catalyze polymer biosynthesis, natural PHA producers have several genes for proteins involved in granule formation and/or with regulatory functions, such as phasins, that have been shown to affect polymer synthesis. This study evaluates the effect of PhaP, a phasin, on bacterial growth and PHB accumulation from glycerol in bioreactor cultures of recombinant Escherichia coli carrying phaBAC from Azotobacter sp. strain FA8. Cells expressing phaP grew more, and accumulated more PHB, both using glucose and using glycerol as carbon sources. When cultures were grown in a bioreactor using glycerol, PhaP-bearing cells produced more polymer (2.6 times) and more biomass (1.9 times) than did those without the phasin. The effect of this protein on growth promotion and polymer accumulation is expected to be even greater in high-density cultures, such as those used in the industrial production of the polymer. The recombinant strain presented in this work has been successfully used for the production of PHB from glycerol in bioreactor studies, allowing the production of 7.9 g/liter of the polymer in a semisynthetic medium in 48-h batch cultures. The development of bacterial strains that can efficiently use this substrate can help to make the industrial production of PHAs economically feasible.